Implementation of individualized educational plan and its challenges i n ngala secondary school for the deaf, nakuru county, kenya - Jebet Nellah, Kipyegon; Bunyasi Awori, Beatrice; Irangi Wamocho, Franciscah (2022)
The study aimed to establish the challenges in the implementation of t he individualized educational plan in schools for students with hearin g impairment at Ngala Secondary School for the Deaf in Nakuru County, Kenya. Data was collected from a target population of ninety-eight stu dents, thirteen teachers and one administrator through purposive and s tratified random sampling techniques. Purposive sampling was used on s chool administrators and teachers to select all 13 teachers and 1 scho ol administrator. On the other hand, stratified random sampling was us ed to select a total of 24 students. The study sample comprised 24 stu dents, 13 teachers and 1 administrator leading to a total of 38 respon dents. The research instrument included the use of questionnaires, int erview schedules and document analysis. A pilot study was conducted at Kedowa Secondary School for the Deaf to enhance the reliability and v alidity of the research instruments. Quantitative data were cleaned, l abelled, coded, entered into a computer and organized using Statistica l Package for Social Sciences (SPSS) version 30. Quantitative data wer e analyzed statistically using descriptive statistics such as percenta ges and frequencies. The analyzed data were presented using tables, ba r-graphs and pie-charts. Qualitative data collected were grouped into different themes, presented as a narrative and discussed based on the objectives of the study. Findings revealed that the major challenge to wards implementation IEP was the lack of adequate teaching and learnin g resources. The study concluded that the major solutions to the chall enges facing teachers in developing and implementing IEP suggest that the provision of adequate resources for IEP were anticipated to enhanc e the academic achievement of students with hearing impairment. The st udy recommended that the Ministry of Education and other stakeholders should help acquire adequate resources for students with hearing impai rment. Article visualizations: